2018
DOI: 10.1016/j.cub.2018.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Dopamine Signals in the Nucleus Accumbens that Cause Active Avoidance Require Endocannabinoid Mobilization in the Midbrain

Abstract: Phasic dopamine (DA) release accompanies approach toward appetitive cues. However, a role for DA in the active avoidance of negative events remains undetermined. Warning signals informing footshock avoidance are associated with accumbal DA release, whereas depression of DA is observed with unavoidable footshock. Here, we reveal a causal role of phasic DA in active avoidance learning; specifically, optogenetic activation of DA neurons facilitates avoidance, whereas optical inhibition of these cells attenuates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 66 publications
12
62
1
Order By: Relevance
“…DA neurons originating in the VTA are known to be modulated by aversive stimuli, and have been implicated in fear conditioning and extinction (El-Ghundi, O'Dowd, and George 2001;Young, Joseph, and Gray 1993;Inoue et al 2000;Nader and LeDoux 1999;Guarraci and Kapp 1999;Holtzman-Assif, Laurent, and Westbrook 2010;Delgado et al 2008;Luo et al 2018;Salinas-Hernández et al 2018;Zweifel et al 2011;Pezze and Feldon 2004;Mueller, Bravo-Rivera, and Quirk 2010;Pignatelli et al 2017;Nasehi et al 2016;Pezze, Bast, and Feldon 2003;Budygin et al 2012;Robinson et al 2019;Lammel et al 2011;Jo, Heymann, and Zweifel 2018;Lutas et al 2019;Fadok, Dickerson, and Palmiter 2009;Groessl et al 2018;Bouchet et al 2018;Wenzel et al 2018;Wang and Tsien 2011;Mileykovskiy and Morales 2011) . However, it was unclear if and how neural correlates of fear extinction are topographically organized within the VTA.…”
Section: Discussionmentioning
confidence: 99%
“…DA neurons originating in the VTA are known to be modulated by aversive stimuli, and have been implicated in fear conditioning and extinction (El-Ghundi, O'Dowd, and George 2001;Young, Joseph, and Gray 1993;Inoue et al 2000;Nader and LeDoux 1999;Guarraci and Kapp 1999;Holtzman-Assif, Laurent, and Westbrook 2010;Delgado et al 2008;Luo et al 2018;Salinas-Hernández et al 2018;Zweifel et al 2011;Pezze and Feldon 2004;Mueller, Bravo-Rivera, and Quirk 2010;Pignatelli et al 2017;Nasehi et al 2016;Pezze, Bast, and Feldon 2003;Budygin et al 2012;Robinson et al 2019;Lammel et al 2011;Jo, Heymann, and Zweifel 2018;Lutas et al 2019;Fadok, Dickerson, and Palmiter 2009;Groessl et al 2018;Bouchet et al 2018;Wenzel et al 2018;Wang and Tsien 2011;Mileykovskiy and Morales 2011) . However, it was unclear if and how neural correlates of fear extinction are topographically organized within the VTA.…”
Section: Discussionmentioning
confidence: 99%
“…Endocannabinoid gating of the mesocorticolimbic dopamine system occurs via inhibition of GABAergic and glutamatergic neurotransmission onto dopamine neurons in the ventral tegmental area (Szabo, Siemes et al 2002, Melis, Pistis et al 2004, Riegel and Lupica 2004, Covey, Mateo et al 2017), by which CB1 receptor activation enhances dopamine release in the striatum (Cheer, Wassum et al 2004, Oleson, Beckert et al 2012). Inverse agonists such as rimonabant counteract endogenous CB1 receptor activation and reduce striatal DA release and cue-motivated behavior (Cheer, Wassum et al 2004, Oleson, Beckert et al 2012), the latter of which is reversed by optogenetic activation of VTA DA neurons (Wenzel, Oleson et al 2018). Further studies are necessary to determine whether VTA CB1 signaling mediates the reported effects on sign-tracking and conditioned reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of phasic dopamine responses to cues reflects the subjectively expected value, such as the amount of reward value, probability of reward delivery, temporal discounting, and distance to the reward . Therefore, the anticipatory activity of dopamine and serotonin can be considered to relay information on future status, which influences decision‐making during goal‐directed behavior and avoidance behavior . In addition to the learning, chronic stress regulates dopamine activity, which may in turn modulate motivation‐related behavior.…”
Section: Sustained Dopamine and Serotonin Effects On Behaviormentioning
confidence: 99%
“…71,72 Therefore, the anticipatory activity of dopamine and serotonin can be considered to relay information on future status, which influences decision-making during goal-directed behavior 10 and avoidance behavior. 73 In addition to the learning, chronic stress regulates dopamine activity, which may in turn modulate motivation-related behavior. For example, a study suggested that chronic mild stress reduced the phasic activities of dopamine neurons in a basolateral-amygdalaand ventral-pallidum-dependent manner.…”
Section: Sustained Dopamine and Serotonin Effects On Behaviormentioning
confidence: 99%